Stan naprężenia w przestrzeni sprężystej wywołany działaniem źródła ciepła zmieniającego się w czasie w sposób harmoniczny - NOWACKI, Witold (Engineering Transactions, 1957)
The state of stress in an elastic space due to a source of heat varying with time in a harmonic manner This paper seeks to determine stresses due to a heat source varying with time in a harmonic manner. A concentrated, linear and plane source is considered in an infinite elastic space. From the solution of the heat equation (1.1), the temperature field is obtained. Using the thermoelastic potential of displacements Φ, related to the temperature by the Eq. (1.8), the stress components σij are found from the Eqs. (1.14). The problem is solved disregarding the inertia forces. It is therefore considered to be a quasi-static problem.